2007
DOI: 10.4269/ajtmh.2007.77.283
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the 45-kD Glycoprotein, Part of a Putative Dengue Virus Receptor Complex in the Mosquito Cell Line C6/36, Is a Heat-Shock–Related Protein

Abstract: Dengue virus (DENV) is transmitted to humans by mosquitoes of the genus Aedes. Although several molecules have been described as part of DENV receptor complex in mosquito cells, none of them have been identified. Our group characterized two glycoproteins (40 and 45 kD) as part of the DENV receptor complex in C6/36 cells. Because identification of the mosquito cell receptor has been unsuccessful and some cell receptors described for DENV in mammalian cells are heat-shock proteins (HSPs), the role of HSPs in DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…More recent future science group www.futuremedicine.com investigations have identified more accurately some cellular proteins with DENV-binding ability in mosquito cells, including a laminin-binding protein, a Hsp90-related protein, prohibitin and a tubulin-like protein [54][55][56][57][58]. Finally, as also shown in mammalian cells, glycosphingolipids specific for mosquito cells were found reactive with DENV-2 [45].…”
Section: Receptors In Mosquito Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…More recent future science group www.futuremedicine.com investigations have identified more accurately some cellular proteins with DENV-binding ability in mosquito cells, including a laminin-binding protein, a Hsp90-related protein, prohibitin and a tubulin-like protein [54][55][56][57][58]. Finally, as also shown in mammalian cells, glycosphingolipids specific for mosquito cells were found reactive with DENV-2 [45].…”
Section: Receptors In Mosquito Cellsmentioning
confidence: 83%
“…Hsp-related protein 45 kD 4 [55] Tubulin-like protein 48 kD 2 [56] Laminin receptor 3, 4 [54] C6/36, CCl-125 (A. aegypti), adult A. aegypti Prohibitin 2 [57,58] AP-61 (A. pseudoculterallis) Glycosphingolipid 2 [45] C6/36, midgut A. aegypti Unknown protein 67-80 kD 1-4 [52] Salivary glands A. aegypti and A. polynesiensis Unknown protein 48-77 kD 1-4 [53] Salivary glands, midgut, ovary A. aegypti Unknown protein 45 kD 4 [51] DC-SIGN: Dendritic cell-specific intercellular adhesion molecule 3-grabbing nonintegrin; GRP-78: Glucose-regulated protein 78; Hsp: Heat-shock protein; TAM: Tyro3, Axl and Mer; TIM: T-cell immunoglobulin and mucin domain containing proteins. Macrophages are also major targets of human infection with DENV and another lectin, the mannose receptor, was identified as a DENV receptor for the four DENV serotypes through binding and functional analyses [33].…”
Section: C6/36 (A Albopictus)mentioning
confidence: 99%
“…Where a more viral rapid replication rate was observed in the mammalian cells after infection with D2-16681, the C6/36 cell line supported a more sustained infection from days 3-7 after infection. The sustained infection may be due to the fact that C6/36 cells harbor a specific laminin-binding protein receptor that may enhance the entry of dengue viruses into the cell (22,23). Furthermore, MMP-2 and MMP-9 were able to enhance viral entry into cells and have been correlated with the pathogenesis of infection (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Other cell surface proteins involved in DENV entry include APO B100 (Guevara et al, 2010), the chemokine receptors CXCR3 and CXCL10 (Ip and Liao, 2010), and stress proteins related to the heat shock family such as GRP78/Bip (Jindadamrongwech and Smith, 2004) and heat-shock protein 70 and 90 (HSP70/90) (Reyes-Del Valle et al, 2005;Reyes-del Valle and del Angel, 2004). In insect C6/36 cells, prohibitin (Kuadkitkan et al, 2010) and the 45-kD heat-shock related glycoprotein (Salas-Benito et al, 2007) have been shown involved in DENV entry. Nevertheless, the exact cell surface proteins serving as receptors/co-receptors for DENV entry is still not well defined.…”
Section: Introductionmentioning
confidence: 99%